HUBUNGAN PENGETAHUAN DAN MOTIVASI SUAMI TENTANG VASEKTOMI DENGAN PENGGUNAAN KB VASEKTOMI DI DESA MENTAYAN WILAYAH KERJA UPT PUSKESMAS SELATBARU KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2016 - Alini Alini; Suprayetno Suprayetno (Jurnal Doppler, 2018)
Vasectomy is a contraceptive that has a high effectiveness (98.85%) in order to prevent pregnancy. BPP and Bengkalis District office data stated that the acceptors of KB vasectomy in 2016 amounted to 8 acceptors, decreased compared to 2014 as many as 43 acceptors. The purpose of this study to determine the relationship of knowledge and motivation of husbands about vasectomy with the use of KB vasectomy. The research design used was quantitative with cross sectional study approach. The population is KK married man in Desa mentayan, sampling by purposive sampling amounting to 78 KK married man eligible vasectomy. The result of univariate analysis is known that the respondent's knowledge about vasectomy is mostly (60,3%), husband's motivation to do vasectomy is mostly negative (64,1%). The result of bivariate analysis using chi square test showed that there was a relationship between husband's knowledge and motivation with the use of KB vasectomy in Mentayan village working area of UPT Puskesmas Selatbaru Subdistrict of Bantan, obtained p value = 0,000 â‰¤ (0,05). It is expected that the BPP and KB Bengkalis regency in order to provide information widely and openly so that people are motivated to use KB vasectomy